Pengaruh Edukasi Melalui Media Leaflet Tentang Pertolongan Pertama Luka Bakar Terhadap Tingkat Pengetahuan Ibu Dengan Anak Balita: The Effect of Education Through Leaflet Media on First Aid for Burns on the Knowledge Level of Mothers with Toddlers - Maulid, Maulid; Aprilia, Hanura; Heriani, Novia; iswantoro, H. (Jurnal Abdi Keperawatan dan Kedokteran, 2026)
Burn injuries in toddlers frequently occur in the household environment and can cause serious consequences if not treated properly. Mothers, as the primary caregivers, play an important role in providing first aid. However, the low level of knowledge regarding the initial management of burn injuries may lead to inappropriate treatment. Education through leaflet media is one effort to improve mothers’ knowledge about first aid for burn injuries in toddlers. This study aimed to determine the effect of education through leaflet media on the knowledge level of mothers with toddlers. This study used a pre-experimental design with a one-group pretest-posttest approach. The sample consisted of 30 respondents selected using a total sampling technique at Pekauman Public Health Center, Banjarmasin. Data were collected using a questionnaire that had been tested for validity (0.470–0.744) and reliability (Cronbach’s Alpha 0.921), then analyzed using the Wilcoxon test. Before the education was provided, most respondents had a moderate level of knowledge (66.7%). After the education, the majority of respondents were in the good knowledge category (66.7%), and there were no respondents in the poor category. The Wilcoxon test showed a p-value of 0.000 (p < 0.05), indicating that education through leaflet media was effective in improving mothers’ knowledge regarding first aid for burn injuries in toddlers. Education through leaflet media proved effective in increasing mothers’ knowledge about first aid for burn injuries in toddlers at Pekauman Public Health Center, Banjarmasin. This study is expected to be considered by health workers in providing routine education to the community.